FLOWERS FROM THE DEVIL: AN AMERICAN OPIATE CRISIS, THE CRIMINALIZATION OF MARIJUANA, AND THE TRIUMPH OF THE PROHIBITION STATE, 1840-1940 - Lawson, Clinton David (2020)
This dissertation focuses on historic changes in public perception of narcotic use and abuse from the mid-nineteenth century to the mid-twentieth. From the 1840s to the outbreak of Civil War, politicians, physicians, the general public, and state and federal government remained largely ambivalent on the topic of drug use. Opium, morphine, and cannabis were legal, widely available in American pharmacies, and touted as essential medicines. Within the Bohemian community, artists and writers experimented with the recreational use of cannabis and their accounts of that style of consumption filled the pages of Harper’s, The New Yorker, and a host of other literary-minded publications. By the 1880s, that seemingly permissive environment seemed to suddenly give way to a government increasingly focused on the regulation and prohibition of drugs. This work argues that a late-nineteenth century opiate epidemic radically transformed the country’s relationship with drugs and placed cannabis on a historical trajectory that led to its criminalization in the late-1930s. As newspapers blamed the perceived narcotic crisis that emerged in post-bellum America on the medical community, public opinion turned, to a large extent, against doctors and pharmacists. This erosion in public trust in the practice of medicine— a direct byproduct of an American opiate crisis—instigated a transfer of control over the nation’s approach to drug management. Once entirely the occupation of a relatively decentralized medical community, crucial choices over the dispensation of narcotics and their general management shifted to the arena of popular politics. This dissertation argues that transference of power aided the formation of a prohibition-minded state that rapidly banned smokable opium, non-medicinal opiates, cocaine, alcohol, heroin, and—eventually—marijuana